PATIENT SATISFACTION WITH INTERPERSONAL COOPERATION AND HEALTH SERVICES AT THE LEVEL OF PRIMARY AND SECONDARY HEALTH CARE - Gora Miljanovic; Damir Pelicic; Anita Kovacic Popovic; Zeljko Vlaisavljevic; Sasa Raıcevıc; Sanja Sofranac; Milena Todorovic (Rojan GÜMÜŞ, 2022)
Interprofessional cooperation and teamwork among health professionals in the health care system are crucial for improving patient satisfaction and quality of health services. The aim of the research is to examine the satisfaction of patients with interpersonal cooperation and health services provided at the level of primary and secondary health care. The research was done as a cross-sectional study and was conducted at the Niksic General Hospital and two health centers in Podgorica. The sample consisted of 154 respondents, both sexes. The research used a questionnaire for health care users designed for the purposes of this research. The questionnaire consists of a general and a specific part. Descriptive statistics measures and x2 test were used for statistical data processing. The results of the research show that there is a statistically significant correlation between gender and patient satisfaction with services χ² (2, N = 154) = 104.117, p = 0.000, as well as between age and patient satisfaction with services χ² (6, N = 154) = 139.294, p = 0.000. Understanding interpersonal cooperation is important for improving the efficiency of health care, its organization and customer satisfaction.